Smart Subsidy? Welfare and Distributional Implications of Malawi's FISP - Jacoby, Hanan (The World Bank, 2016)
It is often argued that subsidizing fertilizer and other inputs is desirable both to boost agricultural production and to help poor farmers. This analysis of Malawi's huge Farmer Input Subsidy Program highlights a tension between these two objectives: The more FISP increases fertilizer use and thereby raises output, the greater the distortion and hence the lower the welfare gains from the program. Indeed, the empirical results indicate that up to 59% of every Kwacha spent on the FISP is wasted, in the sense that the fertilizer is not sufficiently valued by the beneficiaries. Cashing out the program is shown to have desirable distributional implications